Space Closure With Bone Limitations - Lu, Chen (International dental journal, 2025)
IntroductionThis case report demonstrates the challenges and management strategy for orthodontic space closure in a periodontally compromised patient with pre-existing alveolar bone deficiencies. The interdisciplinary approach combining periodontics and orthodontics was critical for achieving successful outcomes while minimizing further bone loss. Case descriptionA 26-year-old female presented with failed extraction space closure after previous orthodontic treatment. Clinical examination revealed chronic periodontitis, Angle Class II malocclusion, and posterior crossbite. CBCT imaging showed significant mandibular anterior bone deficiency with fenestration/dehiscence. Treatment involved initial periodontal therapy followed by modified orthodontic mechanics emphasizing posterior protraction to protect compromised anterior teeth, along with strategic third molar extraction. DiscussionThe case highlights three key considerations: 1) the necessity of 3D imaging for accurate diagnosis of bone morphology, 2) the importance of customized biomechanics to avoid aggravating bone defects, and 3) the essential role of periodontal stability before and during orthodontic treatment. The posterior-driven space closure approach proved effective in this high-risk case. Conclusion/clinical significanceThis successful outcome underscores that careful treatment planning and execution can achieve proper space closure even in periodontally compromised patients. The case establishes a protocol for managing similar challenging cases through interdisciplinary collaboration and biologically-conscious mechanics.